Inhibitors and Breakers of Advanced Glycation Endproducts (AGEs): A Review - Rahbar, S.; Figarola, J.L. (Current Medicinal Chemistry - Immunology, Endocrine & Metabolic Agents, 2002)
Advanced glycation end products (AGEs) are a complex, heterogeneous, sugar derived protein modification that have been implicated in the pathogenesis of diabetic complications, atherosclerosis, Alzheimer's disease and in the process of normal aging. A large number of compounds as inhibitors of glycation and AGE-protein crosslink formation have been reported and currently being developed by us and others. We have previously reported two new classes of compounds; aryl-(and heterocyclic) ureido and aryl (and heterocyclic) carboxamido phenoxy isobutyric acids, and benzoic acid derivatives and related compounds as novel inhibitors of glycation and AGE formation. Additionally, investigation for selectively cleaving and breaking the existing AGEderived cross-links on tissue proteins by pharmacological strategies has been started. Most recently, we have developed several compounds with the ability of breaking AGE-protein cross-links that form in vitro with collagen and βamyloid peptides, and in vivo with collagen and IgG on the surface of red blood cells of induced diabetic rats. Evidence is that both chelation of transition metals and trapping of reactive carbonyl or dicarbonyl intermediates are involved in the mechamisms of action of these novel AGE-inhibitors and breakers. Here we review the inhibitors of glycation and AGEbreakers published to date and describe a number of new inhibitors and AGE-cross-link-breakers not reported previously. These “AGE-inhibitors” and “AGE-breakers” may find therapeutic use in the treatment of diseases that AGE-formation and accumulation may be responsible for their pathogenesis such as diabetes, Alzheimer's, rheumatoid arthritis and atherosclerosis.
Keywords: age breaker